Dental fluorosis, unguided flouride dosing and oral health advocacy practitioners perception of the emerging paradigm - Madukwe IU (Ibom Medical Journal, 2016)
Background Oral health day is an international day to highlight the benefits of a healthy mouth and to promote worldwide awareness of issues around oral health.  In Nigeria oral health policy was developed by the Federal Ministry of Health, approved by the National Council on Health and launched in November 2012.